Study Influence of the Fusible Interfacing to Some Characteristics of the Shirt Collar - Le, Phuc Binh; Bui, Quang Lap (Old Journal, 2018)
The purpose of the article is to study the influence of the fusible interfacing on the characteristics of the fusible interfacing laminated shirt collar, and the relationship between some specification of the fusible interfacing and of the collar fabric and use them as a basis to select the appropriate fusible interfacing for the collar fabric. The results of this study showed that: The choice of the fabric cover of the background fabric in the fusible interfacing is smaller than that of the collar fabric, has limited the filling of the adhesive into the gap between the yarns on the collar fabric. After the fusible interfacing is laminated onto the collar fabric, the thickness of collar fabric increased about two times, the fusible interfacing binds to the collar fabric on each intersection of its warp and weft yarn. About 50% of the surface area between the fusible interfacing and fabric is not covered with glue. This non-glue area creates the ventilation and soft feel needed by the collar. The flexural rigidity of the collar fabric in the direction of the warp yarn is increased about 20÷34 times, in the direction of the weft yarn increased about 6÷15 times. The increase in thickness and flexural rigidity leads to increase of the wrinkle resistance, the crease resistance for the collar fabric and the shape stability for the shirt collar.